2020
DOI: 10.7150/jca.44447
|View full text |Cite
|
Sign up to set email alerts
|

Do Higher Radiation Doses with Concurrent Chemotherapy in the Definitive Treatment of Esophageal Cancer Improve Outcomes? A Meta-Analysis and Systematic Review

Abstract: Background: To investigate the effects and safety profile of radiation dose escalation utilizing computerized tomography (CT) based radiotherapy techniques (including 3-Dimensional conformal radiotherapy, intensity-modulated radiotherapy and proton therapy) in the definitive treatment of patients with esophageal carcinoma (EC) with definitive concurrent chemoradiotherapy (dCCRT). Methods: All relevant studies utilizing CT-based radiation planning, comparing high-dose (≥ 60 Gy) versus standard-dose (50.4 Gy) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In NCCN EC guidelines [14] recommend the radiation dose of 50 or 50.4 Gy for definitive chemo-radiotherapy, radiation dose escalation in the treatment of EC should be studied further. In the recent meta-analysis of trials [24] comparing high-dose (≥ 60 Gy) versus standard-dose (50.4 Gy) radiation for patients with EC, the high-dose group demonstrated a significant improvement in Local-Regional Failure (LRF) (OR 2.199, 95% CI 1.487-3.253; P<0.001), two-year localregional control (LRC) (OR 0.478, 95% CI 0.309-0.740; P=0.001), two-year OS (HR 0.744, 95% CI 0.657-0.843; P<0.001) and five-year OS (HR 0.683, 95% CI 0.561-0.831; P<0.001) rates relative to the standard-dose group. In addition, there was no difference in grade ≥ 3 radiation-related toxicities and treatment-related deaths between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…In NCCN EC guidelines [14] recommend the radiation dose of 50 or 50.4 Gy for definitive chemo-radiotherapy, radiation dose escalation in the treatment of EC should be studied further. In the recent meta-analysis of trials [24] comparing high-dose (≥ 60 Gy) versus standard-dose (50.4 Gy) radiation for patients with EC, the high-dose group demonstrated a significant improvement in Local-Regional Failure (LRF) (OR 2.199, 95% CI 1.487-3.253; P<0.001), two-year localregional control (LRC) (OR 0.478, 95% CI 0.309-0.740; P=0.001), two-year OS (HR 0.744, 95% CI 0.657-0.843; P<0.001) and five-year OS (HR 0.683, 95% CI 0.561-0.831; P<0.001) rates relative to the standard-dose group. In addition, there was no difference in grade ≥ 3 radiation-related toxicities and treatment-related deaths between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…The reason likely was that the radiation dose of the present study was different from the PRODIGE5/ACCORD17 trial. A larger meta-analysis ( 23 ) reported that CCRT with doses of ≥60 Gy for ESCC patients might improve locoregional control and survival compared with the standard-dose CCRT. More than half of the patients received the prescribed total dose of ≥60 Gy, whereas the PRODIGE5/ACCORD17 trial used the standard dose radiation (50 Gy) with a conventional fraction.…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have reported the rate of local control following re-irradiation therapy in patients with LRESCC. Although previous studies have reported that higher radiation doses can improve the local control rate of esophageal cancer and survival rate [ 21 , 22 ]. In the present study, the 3-year locoregional control rate in the LD group and HD group was 3.4% and 14.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%